The effectiveness of inter-teaching: Some international evidence (Journal of Applied Learning and Teaching, 2019)
This study compares final grade results across two different cohorts of accounting students (one using a traditional lecture model and the other inter-teaching – an innovative pedagogy). Boyce and Hineline (2002) designed inter-teaching to engage students in their learning and enhance their academic performance. Accounting courses historically have had a record of high failure rates at an offshore campus of an Australian University, in Vietnam. Final grade comparisons were made between students exposed to inter-teaching and those taught under a traditional lecture-tutorial model. The treatments and participants were independent of each other; however, the course material, assessment and instructor, for both teaching methods, were the same. Both teaching methods were measured for impact in relation to academic performance effectiveness and compared for any differences. The students exposed to inter-teaching performed statistically significantly better than those taught under the traditional model. The findings suggest that inter-teaching is an important tool to encourage the development and improvement of student learning performance, increases student accountability for their learning and advances academic performance in accounting courses.